Assessing the Environmental and Social Benefits of E-Invoicing in Multinational Corporations : The Role of Stakeholder Engagement and Change Management in SAP’s German Operations - Zakharova, Alina; Kania, Karolina Anna; Ali, Tanweer; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis examines how the introduction of e-invoicing in SAP’s German operations contributes to environmental and social sustainability while improving operational efficiency. Using Freeman’s Stakeholder Theory and change management frameworks, the research analyses how the involvement of employees, customers, suppliers, regulators, and internal project teams shapes the success of this digital transformation. A qualitative case study design combines internal project documents and operational data with nine semi-structured interviews conducted with key stakeholders from finance, IT, master data, order-to-invoice, and selected suppliers. The study evaluates measurable outcomes such as reductions in paper use and processing times, as well as perceived changes in workload, job quality, collaboration, and the integration of sustainability into everyday routines.
Vedoucí práce: Karolina Anna Kania
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: sustainability management [obor dipl. práce]; diplomové práce; master's theses